Some physical investigations on silver-doped ZnO sprayed thin films. (February 2015) - Karyaoui, M.; Mhamdi, A.; Kaouach, H.; Labidi, A.; Boukhachem, A.; Boubaker, K.; Amlouk, M.; Chtourou, R.
Abstract: The spray chemical route is used to prepare undoped and Ag-doped ZnO thin films using zinc acetate dehydrate isopropyl alcohol and silver nitrate as doping element in starting solution. XRD analysis shows that all films crystallize in a hexagonal würtzite structure with a preferential orientation along (002) direction. Similarly, the variation in peak positions of X-ray diffraction shows that the silver element is well incorporated into ZnO matrix and not remains in the interstitial sites. Surface morphology studies showed that an increase in the concentration doping causes an increase in the grain size and the mean square roughness R q . Finally, the optical analysis via the transmittance and the reflectance measurements reveals that the bandgap energy E g decreases from 3.29 to 3.25 eV in terms of Ag content.